Investigation of identity’s peculiarities of the women with PCOS - M. Y. Kuzmin; L. V. Suturina (Acta Biomedica Scientifica, 2018)
The aim of the research was studying of identity peculiarities of the women with polycystic ovarian syndrome (PCOS). The authors give a brief review of approaches to the problem in Russian and foreign science. We used the following methods: SEl-test by Soldatova, Life-line by Kronic and Twenty Statements Test by Kuhn&McPartland with the authors' system of processing on the sample of 100 women of reproductive age (50 - with PCOS in accordance with Rotterdam consensus on PCOS and 50 - without PCOS). We have received the following data. The women with PCOS demonstrated a better formed ego-identity (t = 2.32, p < 0.02) and fewer features of identity crisis (t = 2.15, p < 0.03) than their peers from the group of the women without PCOS. They demonstrate more responsibility for their choices and they have better understanding of their emotions and better control over them. Moreover, the women with PCOS have lower tendency to use gender categories (z = 4.32, p < 0.01), family sphere categories (z = 2.7, p < 0.01) and pay more attention to the spheres connected with social identity (carrier, self-development etc.) when self-describing. The data obtained well correlated with the ones obtained earlier, the fact that women with PCOS are more motivated for overcoming stressful situations and the fact that all changes in life, both positive and negative, favor their development.